2010
DOI: 10.1007/s00432-010-0936-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of EphA2 expression in squamous-cell carcinoma of the head and neck

Abstract: These findings suggested that EphA2 may contribute to SCCHN progression and represent a novel prognostic indicator for patients with SCCHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
(39 reference statements)
1
22
0
Order By: Relevance
“…Recent studies in our laboratory have demonstrated that EphA2 overexpression was signiWcantly associated with SCCHN aggressive behavior and poor prognosis from the analysis of clinical tissue specimens (Liu et al 2011). Similar results in clinical tissue level have been obtained by other investigators (Wu et al 2011;Shao et al 2008;Rivera et al 2008).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Recent studies in our laboratory have demonstrated that EphA2 overexpression was signiWcantly associated with SCCHN aggressive behavior and poor prognosis from the analysis of clinical tissue specimens (Liu et al 2011). Similar results in clinical tissue level have been obtained by other investigators (Wu et al 2011;Shao et al 2008;Rivera et al 2008).…”
Section: Introductionsupporting
confidence: 73%
“…In our previous publication (Liu et al 2011), close associations between the expression of EphA2 protein and several clinicopathological parameters, such as tumor site, T classiWcation, clinical stage, recurrence and lymph node metastasis, have been clearly conWrmed in a relative large SCCHN tissue specimens. Moreover, overexpression of EphA2 predicts a poor prognosis in patients with SCCHN.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous investigations have clearly demonstrated EphA2 overexpression in human laryngeal and hypopharyngeal squamous cell carcinoma, and EphA2 regulation of the growth and cervical lymph node metastasis of human laryngeal and hypopharyngeal squamous cell carcinoma in vitro and in vivo (20,22). Although NPC is also classified as a subtype of head and neck squamous cell carcinoma, it possesses unique and distinct epidemiology, clinical characteristics, etiology and histopathology (2).…”
Section: Discussionmentioning
confidence: 99%
“…The western blot analyses were performed as described in previous studies (19,20). In brief, total protein (50 µg/sample) was extracted and separated by 12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and then transferred onto PVDF membranes (Millipore, Bedford, MA, USA).…”
Section: Introductionmentioning
confidence: 99%